RESEARCH OF THERMAL ANALYSIS OF POLYETHYLENE COMPOSITES BASED ON CARBON NANOTUBES (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
In this article, composite materials based on carbon nanotubes were obtained. DTA and TGA analyzes of differential thermal analysis of composite materials obtained on the basis of this polyethylene were studied. According to the obtained results, when 0.01% of carbon nanotubes are added to 1561 polyethylene, the PE liquid temperature increases from 105 to 131°C. It was also observed that the temperature increased to 136.17 °C when carbon nanotubes modified with triethylamine were added.